2018
DOI: 10.1002/jsde.12198
|View full text |Cite
|
Sign up to set email alerts
|

How Does the Surface Activity of Soapwort (Saponaria officinalis L.) Extracts Depend on the Plant Organ?

Abstract: Soapwort (Saponaria officinalis, L) extracts from different plant organs (roots/rhizomes, stems, leaves, and flowers/fruits) were tested because of their ability to lower surface tension at the water/air interface and because of their foaming ability. In addition, surface dilational rheology of the adsorbed layers was assessed. The plant material was collected from May to October 2016 to enable analysis of temporal changes in surface activity of the extracts throughout the same vegetation period. Each organ sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 52 publications
(78 reference statements)
0
2
0
Order By: Relevance
“…Depending on their sources, saponins can vary greatly in terms of molecular formula, ionic properties and surface activity 58–60 . The results of previous research on saponin extracts have evidenced that they are a mixture of different components with a molecular weight of 1070 to 1700 g mol −1 61 .…”
Section: Resultsmentioning
confidence: 99%
“…Depending on their sources, saponins can vary greatly in terms of molecular formula, ionic properties and surface activity 58–60 . The results of previous research on saponin extracts have evidenced that they are a mixture of different components with a molecular weight of 1070 to 1700 g mol −1 61 .…”
Section: Resultsmentioning
confidence: 99%
“…Lyso-bis-phosphatidic acid (LBPA), for example, was shown to be required for the release of phosphorothioate antisense oligonucleotides (PS-ASOs) from late endosomes [ 29 ] and is important for membrane deformation and fusion [ 30 ]. Goral et al [ 31 ] suggested that the interaction of saponins with phospholipids might be equally as important as their affinity for cholesterol, based on their previous studies of the interaction of digitonin with phosphatidylethanolamine (PE) and phosphatidylserine PS [ 32 ] and Quillaja bark saponins with dipalmitoylphosphatidylcholine (DPPC) [ 33 ].…”
Section: Discussionmentioning
confidence: 99%